Validity and Reliability of Least Preferred Coworker (LPC) Scale - Arjanto, Paul; Burhanuddin, Burhanuddin; Sumarsono, Raden Bambang (Faculty of Education Universitas Negeri Malang, 2022)
The purpose of this study was to test the validity and reliability of the Least Preferred Coworker (LPC) Scale in Indonesia. LPC is a self-report instrument that measures the level of relationship between coworkers. Validation was carried out with a sample of 244 respondents spread throughout Indonesia. The results showed that the LPC has a reliability index with Cronbach's Alpha is 0.754 and the validity by factor analysis shows KMO and Bartlett's Test 0.818 with a significance of 0.000 and an anti-image correlation value > 0.5. Formed 1 factor that can explain 46.875% of the variability. factor loading ( factor loading ) of each item between 0.186 - 0.808. The results of this study indicate that LPC can be used as a valid and reliable instrument for measuring the level of relationship between coworkers.